2015
DOI: 10.2341/14-019-lit
|View full text |Cite
|
Sign up to set email alerts
|

White Diet: Is It Necessary During Tooth Whitening?

Abstract: Patients are sometimes blamed for a reduced effect of bleaching when they do not adhere to a dentist's prescribed white diet. This study aimed to determine whether a white diet is necessary by evaluating the effects of coffee, tea, wine, and dark fruits on the potential tooth whitening during the bleaching process. Each of the effects of discoloration was categorized as "yes" or "no" based on a patient questionnaire. Data from five published studies were included in the analyses. Outcomes were based on the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 13 publications
3
16
0
22
Order By: Relevance
“…These results are consistent with other studies (BRISO et al, 2016. MATIS et al 2015 which reported that dark beverages do not negatively influence the overall tooth color change final values.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with other studies (BRISO et al, 2016. MATIS et al 2015 which reported that dark beverages do not negatively influence the overall tooth color change final values.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were not found in the literature, since the studies have limited most of these investigations to a few staining agents (BRISO et al, 2016. MATIS et al 2015SEVEN, 2014.…”
Section: Discussionsupporting
confidence: 38%
“…O clareamento caseiro consiste em uma técnica de baixo custo e pouco tempo de consultório, sendo indicada para dentes com manchamentos médios. São realizadas uma consulta para confecção das moldeiras individuais, orientações sobre como manipular o gel clareador e informações sobre a utilização do produto clareador (MATIS et al, 2015).…”
Section: )unclassified
“…Se ha reportado que ciertas sustancias, principalmente alimentos y bebidas oscuras como el café, vino tinto, té, gaseosa y bebidas energizantes pigmentan los dientes (Pirolo et al;Matis et al, 2015;Briso et al, 2016). Estos cambios pueden estar asociados a pigmentos que se adhieren en la superficie dental (Azer et al, 2011) pero diversos autores refieren que el cambio de color de los dientes va a depender de diferentes factores, unos propios de la solución pigmentante (Berger et al, 2008;Attia et al, 2009;Azer et al;Erdemir et al, 2012;Côrtes et al, 2013;Karadas & Seven, 2014) y otros dependiendo de la propia estructura dental.…”
Section: Introductionunclassified